Viskositas dan Total Padatan Yogurt Susu Kambing dengan Penambahan Ekstrak Daun Kelor (Moringa oleifera) - Nur Hasanah Damayanti; Triana Setyawardani; Kusuma Widayaka (ANGON: Journal of Animal Science and Technology, 2020)
Background. The research objective was to determine the effect of adding Moringa oleifera leaf extract on the viscosity and total solids of goat milk yogurt, and to determine the best percentage of adding Moringa leaf extract to goat milk yogurt. Materials and methods. 10 liters of goat milk, yogurt starter, skim milk, water and moringa leaf extract. The research was conducted using a completely randomized design method (CRD) 4 treatments and 5 repetitions. Treatment R0: Goat milk + 5% yogurt starter + 0% Moringa leaf extract; R1: Goat milk + 5% yogurt starter + 4% Moringa leaf extract; R2: Goat milk + 5% yogurt starter + 8% Moringa leaf extract; and R3: Goat milk + 5% yogurt starter + 12% Moringa leaf extract. The variables measured in the study were viscosity and total solids. Further tests were carried out using the Orthogoal Polynomial Test. Results. The results showed that the addition of Moringa leaf extract to goat's milk yogurt had a very significant effect (P <0.01) on viscosity, and had no significant effect (P> 0.05) on total solids. The average viscosity of yogurt with the addition of Moringa leaf extract was R0 = 456.72 mPa.s; R1 = 98.53 mPa.s mPa.s; R2 = 498.48 mPa.s and R3 = 488.07 mPa.s. The total solids average was R0 = 15.87%; R1 = 15.38%; R2 = 15.08% and R3 = 15.09%. Further test using orthogonal polynomial test, the effect of adding Moringa leaf extract to the viscosity of R2 = 46.96%, and obtained a line equation, namely y = -0.34 x2 + 8.8311x + 441.52. Conclusion. the addition of Moringa leaf extract with different concentrations increased the viscosity of yogurt, but the total solids were relatively the same. The best viscosity was added to yogurt with 4% Moringa leaf extract, with an average of 498.53 ± 0.10 mPa.s.